2021
DOI: 10.3174/ajnr.a7091
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Brain TOF-MRA with Compressed Sensitivity Encoding: A Multicenter Clinical Study

Abstract: BACKGROUND AND PURPOSE:The clinical practice of three-dimensional TOF-MRA, despite its capability in brain artery assessment, has been hampered by the relatively long scan time, while recent developments in fast imaging techniques with random undersampling has shed light on an improved balance between image quality and imaging speed. Our aim was to evaluate the effectiveness of TOF-MRA accelerated by compressed sensitivity encoding and to identify the optimal acceleration factors for routine clinical use. MATE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Nonetheless, in 89.3% of readings the parent vessel was equally visualized on both sequences and in one case it was better depicted on CS TOF images. Previous studies showed that CS TOF MRA may result in worse visualization of smaller vessels compared to PI TOF MRA [21,28], therefore our results could be better explained by the small diameter of the stented vessels rather than the presence of susceptibility artifact due to the stent itself. This hypothesis is also supported by the observation that in the majority of cases in which CS TOF images showed a worse depiction of vascular structures adjacent to the aneurysm dome, the affected vessel was the anterior choroidal artery, which has a smaller diameter compared to the other examined vessels (Figure 4B,E).…”
Section: Discussionmentioning
confidence: 67%
“…Nonetheless, in 89.3% of readings the parent vessel was equally visualized on both sequences and in one case it was better depicted on CS TOF images. Previous studies showed that CS TOF MRA may result in worse visualization of smaller vessels compared to PI TOF MRA [21,28], therefore our results could be better explained by the small diameter of the stented vessels rather than the presence of susceptibility artifact due to the stent itself. This hypothesis is also supported by the observation that in the majority of cases in which CS TOF images showed a worse depiction of vascular structures adjacent to the aneurysm dome, the affected vessel was the anterior choroidal artery, which has a smaller diameter compared to the other examined vessels (Figure 4B,E).…”
Section: Discussionmentioning
confidence: 67%
“…Yamamoto et al compared CS TOF-MRA with different acceleration factors (CS 3 versus CS 5) for evaluating collaterals in MMD patients. They found that CS with lower acceleration factor (CS 3) better visualized Moyamoya collaterals [ 19 ].Another studies of Fushimi et al and Ding et al also supported that small arteries (anterior choroidal arteries, distal branches like A2/3, M4, P4 segments) could be better visualized by CS TOF-MRA with an acceleration factor less than 6 [ 18 , 26 ]. Therefore, considering that the bypass and collateral vessels are all with small size, we set the acceleration factor as 5.…”
Section: Discussionmentioning
confidence: 97%
“…Image artifacts may appear as ghosts inside or outside the ROI if the SENSE acceleration factor is too high ( 23 ). A previous study mentioned that specked noise and SENSE artifacts were observed in the central area of 3D time-of-flight (TOF) MRA images with a large SENSE factor = 4, while these artifacts were rarely found on the images acquired by C-SENSE acceleration ( 24 ). In this study, the source images of 4D-PACK with C-SENSE with 5, 6.5, and 8 showed reduced artifacts compared with the artifacts present when SENSE4.5 was used.…”
Section: Discussionmentioning
confidence: 99%